Between regression and apathy:: educational broadcasting in Temer and Bolsonaro governments - Penna Pieranti, Octavio (2024)
Educational broadcasting is identified with the birth of broadcasting itself and its history is marked by the political use of stations. In Dilma Rousseff government (2011-2016), however, important milestones were established, such as the National Grant Plans and the definition of criteria that favored public entities regarding new stations. This article aims to analyze the initiatives of the Temer (2016-2018) and Bolsonaro (2019-2022) governments related to educational broadcasting. It is pointed out that these governments reduced the possibilities of new stations and did not resolve structuring issues for this segment.